2019
DOI: 10.3389/fmicb.2019.00188
|View full text |Cite
|
Sign up to set email alerts
|

Salinity-Mediated Increment in Sulfate Reduction, Biofilm Formation, and Quorum Sensing: A Potential Connection Between Quorum Sensing and Sulfate Reduction?

Abstract: Biocorrosion in marine environment is often associated with biofilms of sulfate reducing bacteria (SRB). However, not much information is available on the mechanism underlying exacerbated rates of SRB-mediated biocorrosion under saline conditions. Using Desulfovibrio (D.) vulgaris and Desulfobacterium (Db.) corrodens as model SRBs, the enhancement effects of salinity on sulfate reduction, N-acyl homoserine lactone (AHL) production and biofilm formation by SRBs were demonstrated. Under saline conditions, D. vul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 64 publications
(93 reference statements)
3
21
0
Order By: Relevance
“…However, the inhibitory effect was no longer observed at the stationary phase. This observation is consistent with that reported in an earlier study (Park et al, 2005; Sivakumar et al, 2019), and it was probably due to the accumulation of enzymatic inhibitors in the culture over time, or to a decrease in the metabolic activities of the cultures at the stationary phase. QQ enzymes should therefore be deployed as an environmentally benign approach for controlling microbe-associated problems at the early stages of growth and biofilm formation.…”
Section: Discussionsupporting
confidence: 93%
“…However, the inhibitory effect was no longer observed at the stationary phase. This observation is consistent with that reported in an earlier study (Park et al, 2005; Sivakumar et al, 2019), and it was probably due to the accumulation of enzymatic inhibitors in the culture over time, or to a decrease in the metabolic activities of the cultures at the stationary phase. QQ enzymes should therefore be deployed as an environmentally benign approach for controlling microbe-associated problems at the early stages of growth and biofilm formation.…”
Section: Discussionsupporting
confidence: 93%
“…In particular, homologs of proteins involved in the QS-controlled phosphorylation cascade (LuxR and LuxO) and in the acyl homoserine lactone (AHL) synthesis were found in D. vulgaris (17,18). This is verified by the detection of different carbon chains of AHLs, including C 8 -AHL, C 10 -AHL, and C 12 -AHL, in pure cultures of D. vulgaris (19,20). Furthermore, it was found that exposing SRB to QS inhibitors in saline conditions diminished biofilm formation, sulfate reduction, and AHL production (20).…”
mentioning
confidence: 82%
“…Bacterial biofilms occur in diverse environments, such as aquifers 1 , rivers 2,3 , hydrothermal springs 4 , within sewer pipelines 5 , in bioremediation plants 6 and various other places. Within these environments the biofilms can be subjected to extreme temperatures 4,7 , variation in physical forces 8 , changes in chemical concentrations 9 , changes in salinity 10 and pH 11 . These extreme conditions impact a biofilm's lifecycle, and yet, they are able to thrive by colonising a variety of surfaces.…”
Section: Introductionmentioning
confidence: 99%